Time-trend and variations in the proportion of second-eye cataract surgery - Bernal-Delgado Enrique; Cots Francesc; Comas Mercè; Román Rubén; Hoffmeister Lorena; Castells Xavier (BMC, 2007)
Abstract Background Despite recommendations for greater use of second-eye cataract surgery and the bilateral progression of the disease, there is a substantial proportion of unmet need for this treatment. Few studies have explored the factors associated with second-eye cataract surgery utilisation. The objective of our study was to estimate the proportion of second-eye cataract surgery, evaluate its time-trend, and explore differences in utilisation by patients' gender, age, and region of residence. Methods All senile cataract surgeries performed between 1999 and 2002 in the public health system of Catalonia (Spain) were obtained from the Minimum Data Set. The proportion of second-eye surgery from November 2000 to December 2002 was calculated. The time-trend of this proportion was characterised through linear regression models with the logarithmic transformation of time. Results The proportion of second-eye surgery was 30.0% and showed an increasing trend from 24.8% (95% Confidence Interval [CI] 21.6; 26.1) in November 2000 to 31.8% (95% CI 31.4; 33.6) in December 2002. This proportion was 1.9% (95% CI 0.9; 2.9) higher in women (p < 0.001) and held constant across time. Male patients aged less than 60 had the lowest proportion (22.6%; 95% CI 22.4; 22.9) and females between 70 and 79 had the highest proportion (27.4%; 95% CI 26.9; 27.9). The time-trend for the proportion of second-eye surgery in those aged over 80 years was greater than for younger ages, showing an increase of 9% at the end of the period for both males and females. Variations between regions decreased over time because regions with the lowest initial proportions of second-eye surgery (approximately 17%) showed a greater increase over the study period. Conclusion We predict greater utilization of second-eye surgery in patients aged 70 to 79 years and in women. A greater increase in the utilisation rates of second-eye surgery is expected in the regions with lower proportions and in older patients. The observed trend suggests that there will be a substantial proportion of unmet need for bilateral surgery.